Analisis Current Ratio, Debt To Equity Ratio, Receivable Turnover, Return On Equity, Dan Price Earning Ratio Sebagai Alat Untuk Menilai Kinerja Keuangan - Bintang Kusucahyo; Lis Lestari Sukartiningsih; Eirene Pricilia Iryanto (Universitas Katolik Widya Karya Malang, 2024)
This research aims to analyze the Current Ratio, Debt to Equity Ratio, Receivable Turnover, Return on Equity, and Price Earning Ratio as tools for assessing the financial performance of cement companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This type of research is a case study using secondary data. The population was 7 companies, sampling using the purposive sampling method selected 4 companies as samples. The library study data collection method uses documentation data collection techniques, and the data analysis technique uses quantitative descriptive. The company that has the best financial performance is PT Indocement Tunggal Prakarsa Tbk seen from the Current Ratio, Debt to Equity Ratio, and Price Earning Ratio which are above the standard ratio, while the company that has less good financial performance is PT Solusi Bangun Indonesia Tbk seen from the ratio. Current Ratio, Debt to Equity Ratio, Receivable Turnover, and Return on Equity are below the standard ratio